Home Networking for Dummies 3rd Edition - Ivens, Kathy (Wiley Publishing, 2011)
As home networking technologies become more affordable and more popular, this new edition of a bestseller introduces readers to the basics of home networking Walks readers through sharing printers or an Internet connection across several computers and explains how game consoles, televisions, and stereos can also be networked Discusses all of the important aspects of having a home network, including planning and installing the network, security, and maintenance This new edition covers Windows XP Service Pack 2 (a significant update for security, compatibility, stability, wired and wireless networking, and broadband changes) and pays special attention to the Windows Firewall Topics include choosing and installing hardware, file sharing, sharing an Internet connection, security, Wi-Fi, and network maintenance